Methotrexate in sarcoidosis: hematologic and hepatic toxicity encountered in a large cohort over a six year period - Baughman, Robert P.; Cremers, Johanna; Harmon, Martina; Lower, Elyse; Drent, Marjolein (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
ABSTRACT. Background: Methotrexate (MTX) is a second line agent for treatment of sarcoidosis. Its long term safety and efficacy in sarcoidosis remains unclear. Methods: This was a retrospective review of patients seen at the University of Cincinnati Sarcoidosis Clinic over a six year period. For each visit, complete blood count, liver function testing, and dosing and outcome of MTX was noted. For efficacy, we compared the outcome of therapy of patients treated with either MTX or infliximab for one year and results scored as improved, stable, or worse. Results: Over six years, 1606 sarcoidosis patients were seen with a total of 13,576 clinical visits. During the study period, 607 patients (38% of total) were receiving MTX and had available blood work. Moderate elevation of alanine aminotransferase (ALT) (>3 time upper limit normal) was seen in nine (1.6%) patients. White blood count of <1500 cells per cu mm was seen in one patient. At six months, over half of the 44 patients treated with infliximab were better, while only 21% of the 47 MTX treated patients were better (Chi square=11.804, p=0.0081). At the 12 month assessment, the infliximab treated patients were still more likely to be better than those treated with MTX (Chi square=11.141, p=0.011). Only 21% of those treated with MTX were worse at twelve months. Conclusion: In our study, MTXtherapy was associated with very few hepatic or hematologic complications. MTXwas less likely than infliximab to improve clinical status. However, only 20% were worse after one year of MTX.